Analysis of the Evidential Strength of Notarial Deeds in the Activities of the Margi Rizki Demak Savings and Loans Cooperative - Kurniati, Novita; Shallman, Shallman; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstrak. This study aims to analyze the evidentiary power of notarial deeds in the legality of the Margi Rizki Demak Cooperative and identify obstacles and solutions in processing notarial deeds for cooperatives. The urgency of this research lies in the strategic role of cooperatives in the Indonesian economy, particularly in supporting a mutual cooperation-based economy. The research method used is a normative and empirical juridical approach, by reviewing applicable regulations and interviews with notaries, cooperative administrators, and related parties. The results show that the Margi Rizki Demak Cooperative still relies on loan agreements with private deeds based on the principle of kinship, even though notarial deeds have stronger legal force in the evidentiary system. The main problems are the lack of understanding among members, the cost of preparation, and complex administrative procedures. Proposed solutions include legal education, administrative digitization, and collaboration with notaries to strengthen the legality and transparency of cooperative transactions.